Literasi Lingkungan Sekolah Melalui Digitalisasi Pendidikan dan Pengembangan Pengelolaan Sampah di MIM Lubuk Banjar - Salsabella, Nalza Agustin; Fitriani, Umi; Sentika, Januantaq; Adanza, Reyllo; Peratama, Nando; Mardalena, Ervin (Indo-MathEdu Intellectuals Journal, 2026)
The Community Service Program (KKN) conducted in Lubuk Banjar Village, Lubuk Raja Subdistrict, aims to enhance environmental literacy in schools through the integration of educational digitalization and waste management at MI Muhammadiyah Lubuk Banjar. This program was carried out by five university students, focusing on digital education for students, the creation of animated video content on environmental literacy, the installation of educational signage on waste management, the production of recycled trash bins made from used paint buckets, and the organization of cleanliness information boards. The implementation methods included observation, socialization, training, and creative implementation based on student participation. The results of the program showed an improvement in students’ understanding of the importance of environmental cleanliness, their ability to sort waste, and their interest in digital-based learning. In addition, the visually engaging and interactive educational media developed had a positive impact on creating a more attractive and sustainable learning environment. This program emphasizes the importance of synergy between digital education and environmental awareness initiatives as an effort to instill environmental care values from an early age in elementary school settings.